ANALISIS KESHAHIHAN KESATUAN NISHAB DENGAN EMAS - A. Sarjan A. Sarjan (At-Taradhi Jurnal Studi Ekonomi, 2012)
Nishab is a concept in Islamic law about the minimum wealth that will make its ownerhaving an obligation to pay the compulsory alms (zakat). A standard for nishab emerges becausethe monetary values of wealth items, whose nishabs have been specified by Sharia, exist. There-fore, the idea to have a unified nishab standard is a product of ijtihad (legal thinking) that regardsthat knowing the rationality behind the obligation to give alms is possible. Islamic legal scholarshave now motivated to conclude that our textually understanding on nishab needs to be reconsid-ered. The present article focuses on the idea of nishab standard and the validity of the use of gold insetting that standard.